2007
DOI: 10.1007/s10620-007-9870-9
|View full text |Cite
|
Sign up to set email alerts
|

Does Mutation of Hepatitis A Virus Exist in North India?

Abstract: SSCP demonstrates no mobility shift in the VP1/P2A region of the HAV genome. No point mutation was observed in the four suspected cases by sequencing. However a large study from different geographical locations is needed to achieve a logical conclusion about the existence of HAV mutation in the Indian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Therefore, nucleotide variations in the central portion of the 5 noncoding region of HAV may influence the severity of hepatitis A [13] . However, a recent study from India reported no evidence of HAV genome variation according to the severity of hepatitis, which warrants further study on the existence of HAV mutations associated with disease severity [14] .…”
Section: Other Extrahepatic Manifestationsmentioning
confidence: 80%
“…Therefore, nucleotide variations in the central portion of the 5 noncoding region of HAV may influence the severity of hepatitis A [13] . However, a recent study from India reported no evidence of HAV genome variation according to the severity of hepatitis, which warrants further study on the existence of HAV mutations associated with disease severity [14] .…”
Section: Other Extrahepatic Manifestationsmentioning
confidence: 80%
“…If a correlation can be confirmed in a large number of patients, the HAV RNA titer and its dynamic changes would be good markers for predicting s-AH. Finally, although a previous article reported that the HAV genotype and genome variations may not be the main factor in AHA severity, we did not determine HAV genotype or viral sequence variations [ 25 27 ].…”
Section: Discussionmentioning
confidence: 99%